Outbreak of Botulism After Consumption of Illicit Prison-Brewed Alcohol in a Maximum Security Prison—Arizona, 2012. (October 2015) - Yasmin, Seema; Adams, Laura; Briggs, Graham; Weiss, Joli; Bisgard, Kris; Anderson, Shoana; Tsang, Clarisse; Henke, Evan; Vasiq, Muhammad; Komatsu, Ken
The authors investigated the second botulism outbreak to occur in a maximum security prison in Arizona within a 4-month period. Botulism was confirmed in eight men aged 20 to 35 years who reported sharing a single batch of pruno made with potatoes. Initial symptoms included blurred vision, slurred speech, muscle weakness, ptosis, and dysphagia. All patients received heptavalent botulinum antitoxin, seven required mechanical ventilation, and all survived. The median incubation period was 29 hours. Sera from all patients and leftover pruno tested positive for botulinum toxin type A. Botulism should be considered among prisoners with cranial nerve palsies and descending, symmetric flaccid paralysis. Prison-brewed alcohol, particularly when made with potatoes, can be a vehicle for botulism and is associated with outbreaks of botulism in prisons.